2003
DOI: 10.1038/sj.bjc.6600820
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin use and cancers of the upper aerodigestive tract

Abstract: The role of aspirin on the risk of cancers of the upper aerodigestive tract was investigated in the combined data of three Italian casecontrol studies, including 965 cases and 1779 hospital controls. The odds ratio was 0.33 for users of X5 years, and 0.51 for X5 years since first use. Data on the role of aspirin on the risk of cancers of the upper aerodigestive tract are scanty, and mainly related to cancer of the oesophagus. In two rheumatoid arthritis cohorts from Finland (Isomäki et al, 1978) and Sweden (Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
66
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 22 publications
1
66
0
1
Order By: Relevance
“…25,[44][45][46][47][48][49][50][51][52][53][54][55] The current study demonstrated risk reductions with regular aspirin use, regardless of the method for quantifying exposure. Daily intake of aspirin ( 7 tablets/week) showed a greater than 50% reduction in risk of developing esophageal cancer, which is consistent with the results from previous systematic reviews.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…25,[44][45][46][47][48][49][50][51][52][53][54][55] The current study demonstrated risk reductions with regular aspirin use, regardless of the method for quantifying exposure. Daily intake of aspirin ( 7 tablets/week) showed a greater than 50% reduction in risk of developing esophageal cancer, which is consistent with the results from previous systematic reviews.…”
Section: Discussionmentioning
confidence: 99%
“…[35][36][37][38][39][40] One previous cohort study found that aspirin use was associated with reduced risk of death among esophageal cancer cases. 41 Although many studies have investigated the effect of NSAID/aspirin use on the risk of developing esophageal cancer in humans, 25,[42][43][44][45][46][47][48][49][50][51][52] results have been inconsistent. In 2 rheumatoid arthritis cohorts, considered to be frequent NSAID users, no significant reduction in risk for esophageal cancer was observed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We reviewed the 128 retrieved abstracts to find relevant papers, reading those in full in which the abstracts were not entirely informative. We also reviewed earlier meta-analyses on aspirin and NSAIDS in relation to oesophageal and gastric cancers (Corley et al, 2003;Gonzalez-Perez et al, 2003;Wang et al, 2003) and other review articles (Baron, 2003;Bosetti et al, 2003). We limited our analysis to papers reporting case -control or cohort studies of the association between the use of either aspirin or non-aspirin NSAIDS and the risk of oesophageal or gastric adenocarcinomas.…”
Section: Meta-analysismentioning
confidence: 99%
“…Studies of animal models and human cancer cell lines have indicated that the potential chemopreventive effect of NSAIDs might extend to oral cancer (Goodin and Shiff, 2004;Wang, 2005), and this year a large phase III prevention trial of COX-2 inhibitors in patients with premalignant oral lesions (leukoplakia) is scheduled to be launched (Nelson, 2006). Interestingly, only a few epidemiological studies have provided data on the relationship between NSAID use and oral cancer, and the data are conflicting (Thun et al, 1993;Bosetti et al, 2003;Sørensen et al, 2003). This paucity of epidemiologic data prompted us to examine the incidence of oral cancer in a large cohort of NSAID users in Denmark.…”
mentioning
confidence: 99%